A review of cloned mobile malware applications for android devices - Baykara, Muhammet; Colak, Eren (Ieee, 2018)
With the increased mobile applications popularity, fraud methods have become a big problem in this area. Every smartphone definitely has at least one mobile application. These applications, which are constantly connected to the Internet, can threaten our security. Unfortunately, mobile applications still have a lot of vulnerabilities. It has been determined that 96% of the security tests on mobile released applications fail at least one test. This paper focuses on the threat of malware cloned applications and the damage caused to the affected Android users. An explanation of how the cloned malware applications affecting Android users is provided. In addition, a presentation of the awareness steps that users can take to notice these applications is given.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: android; mobile operating systems; malware; mobile security; mobile vulnerabilities; cloned applications